Exergy for A Better Environment and Improved Sustainability 2 Applications (Green Energy and Technology,, 2018)
This multi-disciplinary book presents the most recent advances in exergy, energy, and environmental issues. Volume 2 focuses on applications and covers current problems, future needs, and prospects in the area of energy and environment from researchers worldwide. Based on selected lectures from the Seventh International Exergy, Energy and Environmental Symposium (IEEES7-2015) and complemented by further invited contributions, this comprehensive set of contributions promote the exchange of new ideas and techniques in energy conversion and conservation in order to exchange best practices in "energetic efficiency". Applications are included that apply to the green transportation and sustainable mobility sectors, especially regarding the development of sustainable technologies for thermal comforts and green transportation vehicles. Furthermore, contributions on renewable and sustainable energy sources, strategies for energy production, and the carbon-free society constitute an important part of this book. Exergy for Better Environment and Sustainablity, Volume 2 will appeal to researchers, students, and professionals within engineering and the renewable energy fields.